ANALYSIS OF CONSUMER ATTITUDE TO PRODUCT ATTRIBUTES OF MADE IN CHINA PRODUCTS - Montolalu, Marvel Mosain (Universitas Sam Ratulangi, 2013)
Consumers have different attitudes toward any kind of product which available in market nowadays. One of the countries that producing a lot of manufactured products in the market today is China. The result of that, many brands in worldwide now has made-in China label in their products. Nowadays, made-in China products can be easily found in market of Indonesia espesially in Manado. The purposed of this research is to know consumer attitudes toward made-in China products based on product attributes (quality, price, and design) and to find which attribute is the dominant attribute that influenced consumer to buy made in China products. Theories supporting this research are consumer attitude and country of origin. The population is people of Manado City who ever used made in China products, with the sample size of 100 respondents. This study was conducted in Manado City. The data was gathered through quesionaires by using likert scale. Fishbein Multiattribute Model used as a tool to conduct this research. The result shows that consumer attitude towards made-in China products in Manado is considered good. Attribute price considered as the most dominant attribute which influenced consumer attitude towards the products because of the low price compared with another products. Â Keywords: consumer attitude, country of origin, product attributes, Fishbein multiattribute model